Husband's Right to Leave in the Context of Wife's Maternity Leave: Analysis of Regulatory Developments and Practices in Indonesia Post-Law No. 13 of 2003 concerning Manpower - Farah Dibah, Nabilah; S, Thamrin; Suparto (International Conference On Law And Social Sciences, 2024)
Labor law protection in Indonesia, especially regarding the right to leave for husbands when their wives give birth, still shows various weaknesses. This research aims to examine the development of regulations and practices on maternity leave rights for husbands after the enactment of Law no. 13 of 2003 concerning Employment. The methodology used is a normative study with a statutory regulatory approach and analysis of relevant literature. The research results show that although there are provisions regarding maternity leave rights for male workers, implementation is still minimal and uneven between the public and private sectors. This inequality has a negative impact on the welfare of working families. This research recommends policy revisions to increase equality and fairness in maternity leave rights in Indonesia.